Dynamics of Development of the Microvasculature and Tissue Structures of the Large Intestine in Case of Sequential Pesticide Poisoning (Texas Journal of Medical Science, 2023)
The ongoing worldwide intensive chemicalization of agriculture leads to the fact that annually a large number of various foreign chemicals (xenobiotics), including pesticides, enter the planet's biosphere, that is, the environment for the habitat of all living things, including humans. As a result of careless handling of pesticides, as well as accidental or intentional ingestion of the drug, acute and subacute poisoning occurn